Implementation of the Student Centered Approach in the 2013 Curriculum in Social Studies Learning - Kamilatul Jannah (Journal of Public Policy Analys, 2023)
This research aims to: 1). Describe the use of Student Centered in the 2013 curriculum in social studies learning. 2). Identifying factors for teachers using Student Centered in the 2013 curriculum in social studies learning. 3). Describe the benefits of using a Student Centered approach in the 2013 curriculum in social studies learning. This research uses a qualitative approach with descriptive research type. The data sources obtained were based on observations, interviews and documentation. The research results show that at MTs. Tarbiyatun Nasyiin 1 Pamekasan uses a student centered approach in the 2013 curriculum in social studies learning using a learning model, namely the cooperative learning model, using the discussion method indirectly to teach cooperation, and creating interaction between students or between teachers, so that students are actively involved in the discussion. The quiz method indirectly teaches responsibility, trains students to express their opinions. Apart from that, there is a project based learning model, where the teacher gives assignments and tries to find pictures, attach them so that they form a project, namely clipping. There are several factors for teachers using a student-centered approach in the 2013 curriculum, namely: making students more active in speaking, asking questions, observing and reasoning, helping teachers to overcome difficulties in learning by using learning models. There are also benefits from using the student centered approach in the 2013 curriculum, namely: The positive impact of student centered is that students are more active in the learning process, both asking questions, observing and collaborating in group discussions. The negative impact of student centered is lack of time, not suitable for students who are not used to being active, independent and democratic.